Contracts and deals in Islamic finance : a user's guide to cash flows, balance sheets, and capital structures - Kureshi, Hussein; Hayat, Mohsin; Ohio Library and Information Network (Singapore : John Wiley & Sons, 2015)
A very accessible and concise guide to Islamic finance Contracts and Deals in Islamic Finance provides a clear breakdown of Islamic financial contracts and deal structures for beginners. The embedded requirements within selected Islamic financial contracts, such as risk weightage, capital structures, creations of cash flows, and balance sheets, are explained fully to provide a solid understanding of the backbone of the industry. Aimed primarily at beginners and those with a background in conventional banking, this book guides readers through the major contracts, how they're applied, and how to
Financial ProductsSale of Equity; Conclusion; Chapter 10 Bai al Urbun; Conclusion; Chapter 11 Ijarah and Its Variants; Normal Ijarah; Accounting Entries for Ijarah Contract; Ijarah Muntahiya Bi Tamleek; Al Ijarah Thumma al Bai (AITAB); Sale and Leaseback; Conclusion; Chapter 12 Wadiah; Forms of Wadiah; Enhancements to Wadiah; Money Creation; Conclusion; Chapter 13 Qard; Applications of the Contract of Qard; Qard as a Deposit Instrument; Recording of Qard; Conclusion; Chapter 14 Mudharabah; Simple Application of Mudharabah; Perpetual Mudharabah; Re-Mudharabah
Includes bibliographical references and index
Keywords: Banks and banking -- Religious aspects -- Islam; Finance -- Religious aspects -- Islam; Contracts (Islamic law); Deals; Contracts; Electronic books; Electronic books; Contracts